Comparison of the effect of easterly and westerly vertical wind shear on tropical cyclone intensity change over the western North Pacific - Wei Na; Zhang Xinghai; Chen Lianshou; Hu Hao (Environmental Research Letters, 2018)
The effects of vertical wind shear (VWS) with different directions on tropical cyclone (TC) intensity change are compared in this statistical study based on TCs occurring between 1982 and 2015 over the western North Pacific (WNP). Results show that a westerly VWS has a much higher correlation (−0.36) with change in TC intensity than an easterly VWS (−0.07) over the WNP, especially south-westerly VWS (−0.43). Sea surface temperature (SST) is found to modulate the effect of VWS on TC intensity change as it has a close relationship with zonal VWS (−0.48). The favorable effect of SST, which increases with increase in easterly VWS, could offset the detrimental effect of VWS, leading to a relatively low correlation coefficient between easterly VWS and TC intensity change. By contrast, westerly VWS increases with decreasing SST, and the largest correlation coefficient appears when SST is around 301 K. Therefore, it is suggested that the direction of VWS as well as its value is taken into consideration in models used to predict TC intensity.